Book Bank Service @ IIT Delhi: A Case Study - Khanchandani, Vanita; Ahmad, Mushtaq; Jain, Monika (Journal of Information and Knowledge, 2018)
The purpose of this paper is to present a detailed case study of book bank service at Central Library IIT Delhi. Book Bank service is an important service provided to the economically poor students. The article presents the usage of book bank service at IIT Delhi by students of B.Tech in the first semester the academic year 2017-18. The data was collected from the LibSys software database and analyzed using different parameters to get a clear picture about the usage of book bank by different categories of students. The results depicted that 1704 books out of 4300 books were issued. The service was mostly utilized by first year students. The study will be helpful to library and information professionals in knowing the procedures to run the book bank scheme and to increase its usage.